Mayo ethnobotany : land, history, and traditional knowledge in northwest Mexico - Yetman, David, 1941- (University of California Press, 2002)
The Mayos, an indigenous people of northwestern Mexico, live in small towns spread over southern Sonora and northern Sinaloa, lands of remarkable biological diversity. This book contains a comprehensive description of northwest Mexico's tropical deciduous forests and thornscrub on the traditional Mayo lands.